Developing interactive worksheet with PBL model to improve students’ critical thinking skills and scientific attitudes - Nurul Istiqomah; Tien Aminatun (Research and Development in Education (RaDEn), 2025)
This research is motivated by the limitations of electronic teaching materials that are contextual to environmental issues around students, resulting in students being less motivated in the learning process which affects students' critical thinking skills and scientific attitudes. This study aims to determine the feasibility and develop an interactive worksheet with a PBL model of environmental pollution material to improve students’ critical thinking skills and scientific attitudes. This study uses a research and development (R&D) approach with the ADDIE model. The research subjects are: (1) material experts, (2) media experts, (3) biology teacher practitioners, and (4) students as a product user. The research method uses a quasi-experiment with a non-randomized control group pretest-posttest design with data collection techniques using test and non-test question instruments. The data analysis technique was carried out descriptively using one-way Manova test to determine the effectiveness of interactive worksheet using SPSS software version 27. The results of this study indicate that the developed product is feasible, practical, and effective to be used to improve students' critical thinking skills and scientific attitudes. This can be seen from the results of the one-way Manova test which is 0.00 <0.05 which means that the application of interactive worksheet with PBL model in improving students' critical thinking skills and scientific attitudes simultaneously. And the results of the effect size test show that the treatment given has a simultaneous effect on critical thinking skills by 60% and scientific attitudes by 39.6%.